Mobilization and deposition of plastic along an estuarine bank during tidal cycles - Rosa Sawan; Périne Doyen; Guillaume Veillet; Florence Viudes; Céline Mahfouz; Rachid Amara (Heliyon)
Estuaries represent a transitional environment between continental and marine areas. Limited studies have evaluated how these complex systems contribute to plastic pollution dynamics at this interface. Here, an in situ experimental study was conducted in the Slack estuary, a small macrotidal estuarine system in northern France, to investigate the mobilization and deposition of plastic debris on an estuarine bank at a daily basis during six complete tidal cycles. To achieve this, plastics (macro, meso and microplastics with size ≥3 mm) of different composition and shape were manually deposited along an estuary bank on three different substrates: vegetation, gravel, and sand. The experimental design aimed to explore the complexity of the mobilization and deposition of plastic debris with regard to hydro-meteorological factors, types of substrates, size and shape of plastics. Results showed that tidal cycles played a significant role in plastic mobilization and deposition on the estuary bank. However, the nature of the substrate directly impacted the mobilization and deposition of plastics and the effect of wind may be particularly important for the deposition of allochthonous plastics. Most plastics (around 94 %, 37.9 ± 1.5 plastics/m2) were found to be mobilized after a complete tidal cycle while an average of 3.33 ± 1.8 plastics/m2 was deposited during the same period. Results suggested that in small macrotidal estuaries, the daily net retention is very limited since most plastics were mobilized after a tidal cycle. However, in vegetated substrate, the daily net retention can be 2 to 3 times higher than in other types of substrates (gravel and sand) highlighting the potential of dense vegetation to serve as a retention area for plastic waste.